An electrolytic etching method for displaying the two-phase microstructure and grain boundaries of duplex stainless steel
Through two-step electrolytic etching, the phase boundary and grain boundary of duplex stainless steel are etched by potassium hydroxide and concentrated nitric acid respectively, which solves the problem of difficult grain boundary display in the prior art and provides a detailed structure of duplex stainless steel Information, supports process optimization and application promotion.
Patent Information
- Application Number
- CN202210356649.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-06
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-04-06
AI Technical Summary
The existing metallographic etching method is difficult to clearly display the two-phase grain boundaries of duplex stainless steel, which affects its grain size and optimizes the rolling process.
Using two-step electrolytic etching method, firstly, 10% to 30% potassium hydroxide aqueous etchant is used to clarify the two-phase phase boundary, and then 60% to 70% concentrated nitric acid etchant is used to etch the grain boundary to reveal the crystal. boundary.
It realizes a clear display of the two-phase structure and grain boundaries of duplex stainless steel, provides detailed information on ferrite and austenite distribution, and supports process optimization and application promotion.
Smart Images

Figure CN114808095B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallographic etching methods, and in particular to an electrolytic etching method for displaying two-phase structures and grain boundaries of duplex stainless steel. Background Art
[0002] Resource-saving duplex stainless steel adopts the strategy of partially replacing the Ni and Mo content with low-cost austenitizing elements N and Mn. Although resource-saving duplex stainless steel is cost-effective due to its low concentration of Ni and Mo, its strength and ductility are superior to ferritic SUS 430, austenitic SUS 304 and other duplex stainless steels with high Ni content, while greatly reducing quality requirements and ensuring good corrosion resistance. In particular, the further strict control of costs and resources in contemporary society has made resource-saving duplex stainless steel gradually emerge. At the same time, because resource-saving duplex stainless steel produces TRIP and / or TWIP effects due to metastable austenite, the mechanical properties have been broken through, expanding its application in some demanding performance fields, and continuously expanding the application range of resource-saving duplex stainless steel.
[0003] The duplex stainless steel sample must be mechanically polished and metallographically etched, and the organization must be observed using an optical metallographic microscope or a scanning electron microscope. Then, the composition and production process are appropriately adjusted to achieve the desired performance. The methods commonly used for metallographic etching of duplex stainless steel are mainly chemical etching and electrolytic etching: chemical etching includes: BerahaⅡetchant (60mL H2O+30mL HCl+1g K2S2O2) method, Chinese patent CN103123318A discloses a duplex stainless steel metallographic etching solution, using a solution with a volume of hydrochloric acid: picric acid: anhydrous ethanol = 5:1:100 for etching; Chinese patent CN106248460A discloses a duplex stainless steel metallographic etching method, using a ferric chloride and hydrochloric acid aqueous solution with a mass concentration of 0.05-0.3% and a pH ≤ 2 to erode the sample, etc.; electrolytic etching includes: oxalic acid electrolytic etching method, potassium hydroxide / sodium electrolytic etching method, ferric chloride electrolytic etching method, etc. However, current etching methods usually obtain the metallographic distribution of one or more phases in the alloy, and can only observe the phase boundary between ferrite and austenite with simple organizational structure distribution, especially the two-phase grain boundary of duplex stainless steel, and observe the grain size and shape. Duplex stainless steel has strict requirements on grain size, so the display technology of two-phase grain boundary is particularly important, which is of great significance for technicians to judge whether parts have coarse grains, optimize rolling process and promote the application of resource-saving duplex stainless steel. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an electrolytic etching method for displaying the two-phase structure and grain boundaries of duplex stainless steel, which can effectively and accurately obtain the two-phase structure and grain boundaries of duplex stainless steel.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The present invention provides an electrolytic etching method for displaying the two-phase structure and grain boundaries of duplex stainless steel, comprising the following steps:
[0007] S1. Prepare electrolytic etchant I and electrolytic etchant II;
[0008] S2. immersing the duplex stainless steel sample in electrolytic etchant I for electrolytic etching;
[0009] S3. The duplex stainless steel sample treated in step S2 is taken out from electrolytic etchant I, washed and dried, and then immersed in electrolytic etchant II for electrolytic etching;
[0010] S4. The duplex stainless steel sample treated in step S3 is taken out from the electrolytic etchant II, and after washing and drying, an etched duplex stainless steel sample is obtained;
[0011] Wherein, the electrolytic etchant I is a potassium hydroxide aqueous solution with a concentration of 10% to 30%, and the electrolytic etchant II is concentrated nitric acid with a volume concentration of 60% to 70%.
[0012] In the present invention, a two-step electrolytic etching method is used to clearly display the two-phase structure and grain boundaries of duplex stainless steel. In the first step, potassium hydroxide aqueous solution is used as electrolytic etchant I, which utilizes the different corrosion resistance of ferrite and austenite, and the characteristics that they are not easily over-corroded in electrolytic etchant I. Through etching, the two-phase boundary can be clearly eroded out with sharp contrast, thereby obtaining a comprehensive and clear ferrite-austenite two-phase distribution; the second step uses concentrated nitric acid as electrolytic etchant II, which can etch the grain boundary, thereby clearly displaying the grain boundary.
[0013] In the present invention, the concentration of the potassium hydroxide aqueous solution in the electrolytic etchant I needs to be controlled at 10% to 30%. If the concentration is too high, the phase boundary between the ferrite and austenite phases will be corroded too deeply, affecting the observation effect; if the concentration is too low, a good corrosion effect cannot be achieved.
[0014] Furthermore, in step S1, when preparing the electrolytic etchant I, the potassium hydroxide used is pure elemental powder and the water is deionized water.
[0015] Since the electrolytic etchant I has a certain temperature after preparation, it needs to be left for a period of time to cool before use. Preferably, after the electrolytic etchant I is prepared, it is left for 30 to 60 minutes to allow the electrolytic etchant I to cool to room temperature.
[0016] Furthermore, in step S1, the concentration of the potassium hydroxide aqueous solution is 15%.
[0017] Furthermore, in step S2, the duplex stainless steel is a resource-saving Mn-N partially or completely replaced Ni-Mo type duplex stainless steel.
[0018] Furthermore, in step S2, the components and mass fractions of the duplex stainless steel are as follows: carbon 0.01-0.05%, chromium 18-25%, manganese 3.0-12.0%, nitrogen 0.1-0.35%, nickel 0.1-2.0%, copper 0.1-3.0%, molybdenum 0.1-0.6%, and the remainder is iron.
[0019] Furthermore, in step S2, the duplex stainless steel sample is firstly polished with sandpaper and then mechanically polished before etching until the polished surface is bright and free of scratches.
[0020] Furthermore, in steps S2 and S3, during electrolytic etching, stainless steel with a Cr content greater than 10% is used as the cathode, and the duplex stainless steel sample is used as the anode.
[0021] Furthermore, in step S2, the voltage of electrolytic etching is 2 to 12 V, the electrolysis time is 10 to 40 s, the electrolysis temperature is 15 to 30° C., and the distance between the sample and the cathode is 4 to 6 cm.
[0022] Furthermore, in step S3, the voltage of electrolytic etching is 1-2V, the electrolysis time is 8-12s, the electrolysis temperature is 15-30°C, and the distance between the sample and the cathode is 4-6cm. Since different materials have different corrosion resistance, it is necessary to select different etching voltages and electrolysis times according to the properties of the material. If the etching voltage is too high or the electrolysis time is too long, it will cause over-corrosion of the phase boundaries and grains, making the metallographic display unclear and unclear. On the contrary, if the etching voltage is too low or the electrolysis time is too short, the phase boundaries and grain boundaries will not be clearly displayed.
[0023] Furthermore, in steps S3 and S4, anhydrous ethanol is used to clean the duplex stainless steel sample.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. In resource-saving duplex stainless steel, ferrite and austenite have different corrosion resistance. The present invention uses common chemical reagents in the laboratory - potassium hydroxide and concentrated nitric acid - as electrolytic etchants, and successfully etches the phase boundary and grain boundary of the two phases through a two-step etching method. Among them, potassium hydroxide aqueous solution (electrolytic etchant I) is used as the ferrite-austenite two-phase boundary etchant. Through the first step of electrolytic etching, the two-phase boundary can be clearly etched out with sharp contrast, thereby obtaining a comprehensive and clear ferrite-austenite two-phase distribution. Then, by using concentrated nitric acid (electrolytic etchant II) for the second step of electrolytic etching, on the basis of the clear two-phase boundary, the grain boundary can be quickly and effectively revealed, and the shape, size and other related information of the ferrite-austenite two-phase grains in the alloy can be obtained, which is not achievable by the usual etching method.
[0026] 2. The present invention provides an important basis for studying the two-phase distribution and grain detail information of duplex stainless steel, and also provides a new method for etching duplex stainless steel, which has important practical application value. It provides a reliable basis for subsequent processing parameters and provides accurate and reliable data parameters for practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a 500-fold metallographic structure picture of the sample of Example 1 of the present invention;
[0028] Figure 2 It is a 200-fold metallographic structure picture of the sample of Example 2 of the present invention;
[0029] Figure 3 It is a 500-fold metallographic structure picture of the sample of Example 3 of the present invention;
[0030] Figure 4 This is a 1000x SEM tissue image of the sample of Example 3 of the present invention;
[0031] Figure 5 It is a 500-fold metallographic structure picture of the sample of Example 4 of the present invention;
[0032] Figure 6 The metallographic structure picture is 500 times larger than that of the sample of comparative example 1 of the present invention;
[0033] Figure 7 It is a 500-fold metallographic structure picture of the sample of comparative example 2 of the present invention. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0036] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0037] Example 1
[0038] The selected material is 20Cr3Mn1Ni resource-saving duplex stainless steel hot-rolled plate, and its composition by mass percentage is: C: 0.02%, Cr: 20%, Mn: 3%, Ni: 1%, Si: 0.35, N: 0.2%, and the balance is Fe; the metallographic microscope model is Leica DM13000H.
[0039] The specific operation steps of this embodiment are as follows:
[0040] Step 1: Prepare metallographic specimens.
[0041] (1) Cut metallographic specimens from hot-rolled plates using a molybdenum wire cutter;
[0042] (2) Use 80#, 180#, 240#, 400#, 800#, and 1000# sandpaper from coarse to fine to polish the observation surface of the metallographic specimen;
[0043] (3) Use a metallographic polishing machine equipped with a velvet polishing cloth to mechanically polish the observation surface of the metallographic sample until the polished surface is bright and scratch-free. The polishing agent used for mechanical polishing is a 1.5 μm diamond spray polishing agent.
[0044] Step 2: Prepare electrolytic etchant.
[0045] Prepare electrolytic etchant I: Use a measuring cylinder to measure 85 ml of deionized water and pour it into a beaker; Use a balance to weigh 15 g of potassium hydroxide solid powder, and use a glass rod to stir continuously while slowly pouring the weighed potassium hydroxide solid powder into the same beaker; Use a glass rod to stir the solution until it is completely mixed. At this time, the etchant has a certain temperature, and the etchant needs to be placed in a room temperature environment for 30 to 60 minutes until the solution cools to 10 to 30 ° C before it can be used.
[0046] Preparation of electrolytic etchant II: Use a measuring cylinder to measure 50 ml of 65-68% concentrated nitric acid.
[0047] Step 3: Use a DC regulated power supply to perform the first step of electrolytic etching on the metallographic sample.
[0048] (1) Immerse the stainless steel rod in electrolytic etchant I and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0049] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant I and connect it to the positive electrode of a DC regulated power supply via a wire to serve as the anode of the electrolytic cell;
[0050] (3) Start electrolysis with an electrolysis voltage of 8 V, an electrolysis time of 25 s, and an electrolysis temperature of 25°C. During electrolysis, the distance between the sample and the cathode is 5 cm. Rinse the sample with anhydrous ethanol and blow dry.
[0051] Step 4: Use a DC regulated power supply to perform the second step of electrolytic etching on the metallographic sample.
[0052] (1) Immerse the stainless steel rod in electrolytic etchant II and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0053] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant II and connect it to the positive electrode of a DC regulated power supply through a wire to serve as the anode of the electrolytic cell;
[0054] (3) Electrolysis was started with an electrolysis voltage of 1.2 V, an electrolysis time of 10 s, and an electrolysis temperature of 25° C. During electrolysis, the distance between the sample and the cathode was 5 cm.
[0055] Step 5: Clean and observe the sample. After the electrolysis is completed, remove the metallographic sample from the electrolytic etchant, rinse the sample with anhydrous ethanol, and then blow dry with a hot air blower. Put the metallographic sample into a metallographic microscope for observation.
[0056] Erosion effect Figure 1 The results show that the duplex stainless steel electrolytically etched by the present invention has sharp contrast between the phases, the grain boundaries are clearly visible, and the etching effect is very good.
[0057] Example 2
[0058] The selected material is 20Cr3Mn1Ni resource-saving duplex stainless steel solution treated plate, and its composition by mass percentage is: C: 0.02%, Cr: 20%, Mn: 3%, Ni: 1%, Si: 0.35, N: 0.2%, and the remainder is Fe; the metallographic microscope model is Leica DM13000H.
[0059] The specific operation steps of this embodiment are as follows:
[0060] Step 1: Prepare metallographic specimens.
[0061] (1) Cut the metallographic specimen from the plate using a molybdenum wire cutter;
[0062] (2) Use 80#, 180#, 240#, 400#, 800#, and 1000# sandpaper from coarse to fine to polish the observation surface of the metallographic specimen;
[0063] (3) Use a metallographic polishing machine equipped with a velvet polishing cloth to mechanically polish the observation surface of the metallographic sample until the polished surface is bright and scratch-free. The polishing agent used for mechanical polishing is a 1.5 μm diamond spray polishing agent.
[0064] Step 2: Prepare the electrolytic etchant
[0065] Prepare electrolytic etchant I: Use a measuring cylinder to measure 85 ml of deionized water and pour it into a beaker; Use a balance to weigh 15 g of potassium hydroxide solid powder, and use a glass rod to stir continuously while slowly pouring the weighed potassium hydroxide solid powder into the same beaker; Use a glass rod to stir the solution until it is completely mixed. At this time, the etchant has a certain temperature, and the etchant needs to be placed in a room temperature environment for 30 to 60 minutes until the solution cools to 10-30°C before it can be used.
[0066] Preparation of electrolytic etchant II: Use a measuring cylinder to measure 50 ml of 65-68% concentrated nitric acid.
[0067] Step 3: Use a DC regulated power supply to perform the first step of electrolytic etching on the metallographic sample.
[0068] (1) Immerse the stainless steel rod in electrolytic etchant I and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0069] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant I and connect it to the positive electrode of a DC regulated power supply via a wire to serve as the anode of the electrolytic cell;
[0070] (3) Start electrolysis with an electrolysis voltage of 8 V, an electrolysis time of 30 s, and an electrolysis temperature of 25°C. During electrolysis, the distance between the sample and the cathode is 5 cm. Rinse the sample with anhydrous ethanol and blow dry.
[0071] Step 4: Use a DC regulated power supply to perform the second step of electrolytic etching on the metallographic sample.
[0072] (1) Immerse the stainless steel rod in electrolytic etchant II and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0073] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant II and connect it to the positive electrode of a DC regulated power supply through a wire to serve as the anode of the electrolytic cell;
[0074] (3) Electrolysis was started with an electrolysis voltage of 1.3 V, an electrolysis time of 10 s, and an electrolysis temperature of 25° C. During electrolysis, the distance between the sample and the cathode was 5 cm.
[0075] Step 5: Clean and observe the sample. After the electrolysis is completed, take out the metallographic sample from the electrolytic etchant, rinse the sample with anhydrous ethanol, and then blow dry it with a hot air blower; put the metallographic sample into a metallographic microscope for observation.
[0076] Erosion effect Figure 2 The results show that the duplex stainless steel electrolytically etched by the present invention has sharp contrast between the phases, the grain boundaries are clearly visible, and the etching effect is very good.
[0077] Example 3
[0078] The selected material is 20Cr3Mn1Ni2Cu resource-saving duplex stainless steel plate after solid solution treatment, and its composition by mass percentage is: C: 0.02%, Cr: 20%, Mn: 3%, Ni: 1%, Cu: 2%, Si: 0.35, N: 0.2%, and the remainder is Fe; the metallographic microscope model is Leica DM13000H.
[0079] The specific operation steps of this embodiment are as follows:
[0080] Step 1: Prepare metallographic specimens.
[0081] (1) Cut the metallographic specimen from the plate using a molybdenum wire cutter;
[0082] (2) Use 80#, 180#, 240#, 400#, 800#, and 1000# sandpaper from coarse to fine to polish the observation surface of the metallographic specimen;
[0083] (3) Use a metallographic polishing machine equipped with a velvet polishing cloth to mechanically polish the observation surface of the metallographic sample until the polished surface is bright and scratch-free. The polishing agent used for mechanical polishing is a 1.5 μm diamond spray polishing agent.
[0084] Step 2: Prepare the electrolytic etchant
[0085] Prepare electrolytic etchant I: Use a measuring cylinder to measure 85 ml of deionized water and pour it into a beaker; Use a balance to weigh 15 g of potassium hydroxide solid powder, and use a glass rod to stir continuously while slowly pouring the weighed potassium hydroxide solid powder into the same beaker; Use a glass rod to stir the solution until it is completely mixed. At this time, the etchant has a certain temperature, and the etchant needs to be placed in a room temperature environment for 30 to 60 minutes until the solution cools to 10-30°C before it can be used.
[0086] Preparation of electrolytic etchant II: Use a measuring cylinder to measure 50 ml of 65-68% concentrated nitric acid.
[0087] Step 3: Use a DC regulated power supply to perform the first step of electrolytic etching on the metallographic sample.
[0088] (1) Immerse the stainless steel rod in electrolytic etchant I and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0089] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant I and connect it to the positive electrode of a DC regulated power supply via a wire to serve as the anode of the electrolytic cell;
[0090] (3) Start electrolysis with an electrolysis voltage of 10 V, an electrolysis time of 25 s, and an electrolysis temperature of 25°C. During electrolysis, the distance between the sample and the cathode is 5 cm. Rinse the sample with anhydrous ethanol and blow dry.
[0091] Step 4: Use a DC regulated power supply to perform the second step of electrolytic etching on the metallographic sample.
[0092] (1) Immerse the stainless steel rod in electrolytic etchant II and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0093] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant II and connect it to the positive electrode of a DC regulated power supply through a wire to serve as the anode of the electrolytic cell;
[0094] (3) Electrolysis was started with an electrolysis voltage of 1.3 V, an electrolysis time of 12 s, and an electrolysis temperature of 25° C. During electrolysis, the distance between the sample and the cathode was 5 cm.
[0095] Step 5: Clean and observe the sample. After the electrolysis is completed, take out the metallographic sample from the electrolytic etchant, rinse the sample with anhydrous ethanol, and then blow dry it with a hot air blower; put the metallographic sample into a metallographic microscope for observation.
[0096] Erosion effect Figure 3 and Figure 4 The results show that in the duplex stainless steel electrolytically etched by the present invention, the contrast between the phases is sharp, the grain boundaries are clearly visible, and the etching effect is very good.
[0097] Example 4
[0098] The selected material is 20Cr6Mn1Ni resource-saving duplex stainless steel hot-rolled plate, and its composition by mass percentage is: C: 0.02%, Cr: 20%, Mn: 6%, Ni: 1%, Si: 0.35, N: 0.2%, and the balance is Fe; the metallographic microscope model is Leica DM13000H.
[0099] The specific operation steps of this embodiment are as follows:
[0100] Step 1: Prepare metallographic specimens.
[0101] (1) Cut metallographic specimens from hot-rolled plates using a molybdenum wire cutter;
[0102] (2) Use 80#, 180#, 240#, 400#, 800#, and 1000# sandpaper from coarse to fine to polish the observation surface of the metallographic specimen;
[0103] (3) Use a metallographic polishing machine equipped with a velvet polishing cloth to mechanically polish the observation surface of the metallographic sample until the polished surface is bright and scratch-free. The polishing agent used for mechanical polishing is a 1.5 μm diamond spray polishing agent.
[0104] Step 2: Prepare the electrolytic etchant
[0105] Prepare electrolytic etchant I: Use a measuring cylinder to measure 85 ml of deionized water and pour it into a beaker; Use a balance to weigh 15 g of potassium hydroxide solid powder, and use a glass rod to stir continuously while slowly pouring the weighed potassium hydroxide solid powder into the same beaker; Use a glass rod to stir the solution until it is completely mixed. At this time, the etchant has a certain temperature, and the etchant needs to be placed in a room temperature environment for 30 to 60 minutes until the solution cools to 10-30°C before it can be used.
[0106] Preparation of electrolytic etchant II: Use a measuring cylinder to measure 50 ml of 65-68% concentrated nitric acid.
[0107] Step 3: Use a DC regulated power supply to perform the first step of electrolytic etching on the metallographic sample.
[0108] (1) Immerse the stainless steel rod in electrolytic etchant I and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0109] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant I and connect it to the positive electrode of a DC regulated power supply via a wire to serve as the anode of the electrolytic cell;
[0110] (3) Start electrolysis with an electrolysis voltage of 10 V, an electrolysis time of 30 s, and an electrolysis temperature of 25°C. During electrolysis, the distance between the sample and the cathode is 5 cm. Rinse the sample with anhydrous ethanol and blow dry.
[0111] Step 4: Use a DC regulated power supply to perform the second step of electrolytic etching on the metallographic sample.
[0112] (1) Immerse the stainless steel rod in electrolytic etchant II and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0113] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant II and connect it to the positive electrode of a DC regulated power supply through a wire to serve as the anode of the electrolytic cell;
[0114] (3) Electrolysis was started with an electrolysis voltage of 1.5 V, an electrolysis time of 12 s, and an electrolysis temperature of 25° C. During electrolysis, the distance between the sample and the cathode was 5 cm.
[0115] Step 5: Clean and observe the sample. After the electrolysis is completed, take out the metallographic sample from the electrolytic etchant, rinse the sample with anhydrous ethanol, and then blow dry it with a hot air blower; put the metallographic sample into a metallographic microscope for observation.
[0116] Erosion effect Figure 5 The results show that the duplex stainless steel electrolytically etched by the present invention has sharp contrast between the phases, the grain boundaries are clearly visible, and the etching effect is very good.
[0117] Comparative Example 1
[0118] The selected material is 20Cr6Mn1Ni resource-saving duplex stainless steel solution treated plate, containing the following components by mass percentage: C: 0.02%, Cr: 20%, Mn: 6%, Ni: 1%, Si: 0.35, N: 0.2%, and the remainder is Fe; the metallographic microscope model is Leica DM13000H.
[0119] The specific operation steps of this embodiment are as follows:
[0120] Step 1: Prepare metallographic specimens.
[0121] (1) Cut metallographic specimens from hot-rolled plates using a molybdenum wire cutter;
[0122] (2) Use 80#, 180#, 240#, 400#, 800#, and 1000# sandpaper from coarse to fine to polish the observation surface of the metallographic specimen;
[0123] (3) Use a metallographic polishing machine equipped with a velvet polishing cloth to mechanically polish the observation surface of the metallographic sample until the polished surface is bright and scratch-free. The polishing agent used for mechanical polishing is a 1.5 μm diamond spray polishing agent.
[0124] Step 2: Prepare the electrolytic etchant
[0125] Prepare electrolytic etchant I: Use a measuring cylinder to measure 85 ml of deionized water and pour it into a beaker; Use a balance to weigh 15 g of potassium hydroxide solid powder, and use a glass rod to stir continuously while slowly pouring the weighed potassium hydroxide solid powder into the same beaker; Use a glass rod to stir the solution until it is completely mixed. At this time, the etchant has a certain temperature, and the etchant needs to be placed in a room temperature environment for 30 to 60 minutes until the solution cools to 10-30°C before it can be used.
[0126] Preparation of electrolytic etchant II: Use a measuring cylinder to measure 50 ml of 65-68% concentrated nitric acid.
[0127] Step 3: Use a DC regulated power supply to perform the first step of electrolytic etching on the metallographic sample.
[0128] (1) Immerse the stainless steel rod in electrolytic etchant I and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0129] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant I and connect it to the positive electrode of a DC regulated power supply via a wire to serve as the anode of the electrolytic cell;
[0130] (3) Start electrolysis with an electrolysis voltage of 10 V, an electrolysis time of 30 s, and an electrolysis temperature of 25°C. During electrolysis, the distance between the sample and the cathode is 5 cm. Rinse the sample with anhydrous ethanol and blow dry.
[0131] Step 4: Use a DC regulated power supply to perform the second step of electrolytic etching on the metallographic sample.
[0132] (1) Immerse the stainless steel rod in electrolytic etchant II and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0133] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant II and connect it to the positive electrode of a DC regulated power supply through a wire to serve as the anode of the electrolytic cell;
[0134] (3) Electrolysis was started with an electrolysis voltage of 1.2 V, an electrolysis time of 12 s, and an electrolysis temperature of 25° C. During electrolysis, the distance between the sample and the cathode was 5 cm.
[0135] Step 5: Clean and observe the sample. After the electrolysis is completed, take out the metallographic sample from the electrolytic etchant, rinse the sample with anhydrous ethanol, and then blow dry it with a hot air blower; put the metallographic sample into a metallographic microscope for observation.
[0136] Erosion effect Figure 6 The results show that the electrolytic etching voltage in the fourth step is not enough, which leads to unclear grain boundaries, so the electrolytic voltage in the fourth step needs to be increased.
[0137] Comparative Example 2
[0138] The selected material is 20Cr3Mn1Ni2Cu resource-saving duplex stainless steel cold-rolled plate, and its composition by mass percentage is: C: 0.02%, Cr: 20%, Mn: 3%, Ni: 1%, Cu: 2%, Si: 0.35, N: 0.2%, and the remainder is Fe; the metallographic microscope model is Leica DM13000H.
[0139] The specific operation steps of this embodiment are as follows:
[0140] Step 1: Prepare metallographic specimens.
[0141] (1) Cut metallographic specimens from hot-rolled plates using a molybdenum wire cutter;
[0142] (2) Use 80#, 180#, 240#, 400#, 800#, and 1000# sandpaper from coarse to fine to polish the observation surface of the metallographic specimen;
[0143] (3) Use a metallographic polishing machine equipped with a velvet polishing cloth to mechanically polish the observation surface of the metallographic sample until the polished surface is bright and scratch-free. The polishing agent used for mechanical polishing is a 1.5 μm diamond spray polishing agent.
[0144] Step 2: Prepare the electrolytic etchant
[0145] Prepare electrolytic etchant I: Use a measuring cylinder to measure 75 ml of deionized water and pour it into a beaker; Use a balance to weigh 25 g of potassium hydroxide solid powder, and use a glass rod to stir continuously while slowly pouring the weighed potassium hydroxide solid powder into the same beaker; Use a glass rod to stir the solution until it is completely mixed. At this time, the etchant has a certain temperature, and the etchant needs to be placed in a room temperature environment for 30 to 60 minutes until the solution cools to 10-30°C before it can be used.
[0146] Preparation of electrolytic etchant II: Use a measuring cylinder to measure 50 ml of 65-68% concentrated nitric acid.
[0147] Step 3: Use a DC regulated power supply to perform the first step of electrolytic etching on the metallographic sample.
[0148] (1) Immerse the stainless steel rod in electrolytic etchant I and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0149] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant I and connect it to the positive electrode of a DC regulated power supply via a wire to serve as the anode of the electrolytic cell;
[0150] (3) Start electrolysis with an electrolysis voltage of 10 V, an electrolysis time of 25 s, and an electrolysis temperature of 25°C. During electrolysis, the distance between the sample and the cathode is 5 cm. Rinse the sample with anhydrous ethanol and blow dry.
[0151] Step 4: Use a DC regulated power supply to perform the second step of electrolytic etching on the metallographic sample.
[0152] (1) Immerse the stainless steel rod in electrolytic etchant II and connect it to the negative electrode of a DC regulated power supply via a wire to serve as the cathode of the electrolytic cell;
[0153] (2) Immerse the polished surface of the metallographic sample in electrolytic etchant II and connect it to the positive electrode of a DC regulated power supply through a wire to serve as the anode of the electrolytic cell;
[0154] (3) Electrolysis was started with an electrolysis voltage of 1.5 V, an electrolysis time of 12 s, and an electrolysis temperature of 25° C. During electrolysis, the distance between the sample and the cathode was 5 cm.
[0155] Step 5: Clean and observe the sample. After the electrolysis is completed, take out the metallographic sample from the electrolytic etchant, rinse the sample with anhydrous ethanol, and then blow dry it with a hot air blower; put the metallographic sample into a metallographic microscope for observation.
[0156] Erosion effect Figure 7 The results show that due to the excessively high concentration of potassium hydroxide aqueous solution in the second step electrolytic etchant I, the two-phase interface is etched too deeply during electrolytic etching; and the etching voltage in the fourth step is too high, resulting in excessive corrosion of the grains, making the metallographic display unclear and unclear.
[0157] In summary, the present invention provides a new duplex stainless steel etching method, which can etch out the phase boundaries and grain boundaries of the two phases respectively through two-step electrolytic etching, thereby obtaining comprehensive and clear ferrite-austenite two-phase distribution, as well as the shape, size and other related information of ferrite-austenite two-phase grains in the alloy.
[0158] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. An electrolytic etching method for displaying the two-phase structure and grain boundaries of duplex stainless steel, characterized in that: The following steps are involved: S1. Prepare electrolytic etchant I and electrolytic etchant II; S2. immersing the duplex stainless steel sample in electrolytic etchant I for electrolytic etching; In step S2, the voltage of electrolytic etching is 2 to 12 V, the electrolytic time is 10 to 40 s, the electrolytic temperature is 15 to 30° C., and the distance between the sample and the cathode is 4 to 6 cm; S3. The duplex stainless steel sample treated in step S2 is taken out from electrolytic etchant I, washed and dried, and then immersed in electrolytic etchant II for electrolytic etching; in step S3, the electrolytic etching voltage is 1 to 2 V, the electrolysis time is 8 to 12 s, the electrolysis temperature is 15 to 30 ° C, and the distance between the sample and the cathode is 4 to 6 cm; S4. The duplex stainless steel sample treated in step S3 is taken out from the electrolytic etchant II, and after washing and drying, an etched duplex stainless steel sample is obtained; Wherein, the electrolytic etchant I is a potassium hydroxide aqueous solution with a mass concentration of 10% to 30%; the electrolytic etchant II is concentrated nitric acid with a volume concentration of 60% to 70%; The components and mass fractions of the duplex stainless steel are as follows: 0.01-0.05% carbon, 18-25% chromium, 3.0-12.0% manganese, 0.1-0.35% nitrogen, 0.1-2.0% nickel, 0.1-3.0% copper, 0.1-0.6% molybdenum, and the balance is iron.
2. The electrolytic etching method for displaying the two-phase structure and grain boundaries of duplex stainless steel according to claim 1, characterized in that: In step S1, after preparing the electrolytic etchant I, let it stand for 30 to 60 minutes.
3. The electrolytic etching method for displaying the two-phase structure and grain boundaries of duplex stainless steel according to claim 1, characterized in that: In step S2, the duplex stainless steel is a resource-saving Mn-N partially or completely replaced Ni-Mo type duplex stainless steel.
4. The electrolytic etching method for displaying the two-phase structure and grain boundaries of duplex stainless steel according to claim 1, characterized in that: In step S2, before etching, the duplex stainless steel sample is firstly polished with sandpaper and then mechanically polished until the polished surface is bright and free of scratches.
5. The electrolytic etching method for displaying the two-phase structure and grain boundaries of duplex stainless steel according to claim 1, characterized in that: In steps S2 and S3, during electrolytic etching, the stainless steel with a Cr mass fraction greater than 10% is used as the cathode, and the duplex stainless steel sample is used as the anode.
6. The electrolytic etching method for displaying the two-phase structure and grain boundaries of duplex stainless steel according to claim 1, characterized in that: In steps S3 and S4, anhydrous ethanol is used to clean the duplex stainless steel sample.
Citation Information
Patent Citations
Method for determining two-phase specific value in double-phase stainless steel
CN103123318A
Measuring method for duplex stainless steel phase content
CN106248460A
Method for displaying two-phase grain boundary of duplex stainless steel
CN103792128A
Etchant and etching method for duplex stainless steel
CN108426883A
Method for displaying grain boundaries of duplex stainless steel thermal deformation recrystallized grains
CN111077005A